Spot protein/creatinine ratio as a marker for fetomaternal outcome in hypertensive disorder of pregnancy - Taneja, Ashima; Kaur, Gagandeep; Kaur, Manpreet; Chaudhary, Muskan; Kaur, Kulvir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Gestational hypertension is defined as systolic BP level of > 140 mmHg or a diastolic BP of > 90 mmHg that occur after 20 weeks of gestation. Pre-eclampsia is the hypertensive disorder of pregnancy, associated with adverse fetomaternal complications. It is assosciated with proteinuria. 24 hours urine collection is cumbersome, time consuming and potentially misleading if collected inaccurately. The spot P/C ratio has been considered equivalent to 24-hour urinary protein for predicting proteinuria. Aim of study was to compare spot P/C ratio to 24 hours urinary protein in patients of pre-eclampsia and to determine the fetomaternal outcome in the patients admitted in Dayanand Medical College and Hospital, Ludhiana. Methods: A prospective simple random study. It included 100 hypertensive pregnant women being evaluated for pre-elampsia, regardless of the alerting signs or symptoms. The main measures were the urinalysis of patients which included urinary spot P/C and 24 hours urinary protein excretion and the fetomaternal outcome in these patients. The data was statistically analyzed. Results: A good positive correlation existed between the P/C ratio and 24 hours protein excretion, with a correlation coefficient (r) of 0.912. The sensitivity and specificity of 24 hours urinary protein versus spot P/C ratio ranged between 86.29%-99.51% and 8.35%-99.95% respectively. The positive and negative likelihood ratio of 24 hours urinary protein versus spot P/C ratio was 48 (ranged between 6.89-334) and 0.04 (ranged between 0.01-0.16) respectively. The positive and negative predictive value of 24 hours urinary protein versus spot P/C ratio was 97.96% and 96.08% respectively. Our data showed that urine spot P/C ratio above 3.9/mg strongly predicts significant proteinuria of more than 4 gram/day. Conclusions: Spot urinary P/C ratio with suspected preeclampsia can be used as a rapid alternative test to 24 hours urinary protein.